Barley lys3 mutants are unique amongst shrunken-endosperm mutants in having abnormally large embryos. (July 2018) - Cook, Frederick; Hughes, Nathan; Nibau, Candida; Orman-Ligeza, Beata; Schatlowski, Nicole; Uauy, Cristobal; Trafford, Kay
Abstract: Many shrunken endosperm mutants of barley ( Hordeum vulgare L.) have been described and several of these are known to have lesions in starch biosynthesis genes. Here we confirm that one type of shrunken endosperm mutant, lys3 (so called because it was first identified as a high-lysine mutant) has an additional phenotype: as well as shrunken endosperm it also has enlarged embryos. The lys3 embryos have a dry weight that is 50–150% larger than normal. Observations of developing lys3 embryos suggest that they undergo a form of premature germination and the mature lys3 grains show reduced dormancy. In many respects, the phenotype of barley lys3 is similar to that of rice GIANT EMBRYO mutants (affected in the OsGE gene). However, the barley orthologue of OsGE is located on a different chromosome from Lys3 . Together these results suggest that the gene underlying Lys3 is unlikely to encode a starch biosynthesis protein but rather a protein influencing grain development.